Factors associated with improvement in activities of daily living (ADL) in stroke patients post domiciliary care in Kelantan - Ismail, Nur Raihan (2018)
Background: Rehabilitation is crucial to assist individuals with stroke to improve activities of daily living (ADL). Despite of comprehensive rehabilitation provision, recognition of the associated factors influence stroke recovery are also important. In Malaysia, domiciliary care service is an outreach home-based rehabilitation, provided by a multidisciplinary rehabilitation team for stroke survivors. However, there has been no study conducted to assess factors associated with improvement in ADL among stroke patients after the rehabilitation service. Objective: To describe the proportion of stroke patients with improved ADL post domiciliary care and to determine the demographic and clinical factors associated with the improvement in ADL among stroke patients post Domiciliary Care in Kelantan. Methodology: This was a cross sectional study, conducted from February until April 2018 using secondary data obtained from Domiciliary Care Referral Letter, Domiciliary Care Patient’s Record (PPD 004 (a)/2014) and Domiciliary Case Assessment Record (PPD 004 (b)/2014) which are used as formal documentations for the domiciliary care in Malaysia. The data from 11 health clinics with comprehensive domiciliary care in Kelantan were collected using a proforma and analysed using IBM SPSS Statistics version 22 software. Descriptive and multiple logistic regression analysis were performed. Improved ADL is defined as at least 30% increment at the end of the service. Results: Between January 2015 and October 2017, there were 384 stroke patients registered in comprehensive domiciliary care service for the state of Kelantan, in which 234 individuals fulfilled the study criteria and were all included in the study. The proportion of stroke patients with improved in ADL was found to be 72.2%, which comprised of 96 (41.0%) of the male population and 138 (59.0%) of females. The mean (SD) age for stroke patients were 68.21 (11.99) years old. One hundred and fifty seven (67.1%) of stroke patients were aged 65 years and above and two third were married (65.8%). Majority of patients had ischemic stroke. Significant association was found between age group (Adj. OR 2.241; 95% CI 1.019, 4.927; p =0.045), ischemic stroke type (Adj. OR 4.842; 95% CI: 2.180, 10.758; p <0.001), less severe stroke (mRS score 4) (Adj. OR 3.492; 95% CI: 1.696, 7.189; p =0.001), no history of previous stroke (Adj. OR 3.702; 95% CI: 1.756, 7.803; p =0.001) and those received ≥8 rehabilitation visits (Adj. OR 2.226; 95% CI: 1.113, 4.450; p =0.024). Conclusion: The young age <65 years old, ischemic type of stroke, less severe stroke (mRS 4), no history of previous stroke and ≥8 rehabilitation visits were found to be significant factors associated with the improvement in ADL post stroke event. Recognition of these factors of stroke recovery is beneficial to intensify an optimal stroke care and rehabilitation services in the country.